2021
DOI: 10.1186/s12889-020-10140-6
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of health-related behaviours within children aged 11–16: a systematic review

Abstract: Objective We aimed to systematically review and synthesise evidence on the clustering of a broad range of health-related behaviours amongst 11–16 year olds. Method A literature search was conducted in September 2019. Studies were included if they used cluster analysis, latent class analysis, prevalence odds ratios, principal component analysis or factor analysis, and considered at least three health-related behaviours of interest among 11–16 year o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…Physical inactivity, poor diet, alcohol use, smoking, poor sleep, and excessive recreational screen time are lifestyle risk factors that emerge during adolescence, continue into adulthood, and often occur together 1 . They are linked with obesity 2 and mental health problems in the short term, 3 and with increased risk of chronic disease in adulthood 4 …”
mentioning
confidence: 99%
“…Physical inactivity, poor diet, alcohol use, smoking, poor sleep, and excessive recreational screen time are lifestyle risk factors that emerge during adolescence, continue into adulthood, and often occur together 1 . They are linked with obesity 2 and mental health problems in the short term, 3 and with increased risk of chronic disease in adulthood 4 …”
mentioning
confidence: 99%
“…Based on cutoff value of 20%, the likely incidence of l-th response to j-th variable in k-th profile among pure types of that profile must be at least 20% higher than the observed marginal likelihood [28,29]. Risk factors coexisted in the current study when there were at least two risk factors for CVD in the generated profile [20].…”
Section: Discussionmentioning
confidence: 90%
“…Thus, it is essential assessing CVD risk factors at this developmental stage, by taking into consideration their coexistence, rather than approaching them in separate. Grouped patterns of health-related risk behaviors often appear in adolescence [17][18][19][20] and the coexistence of these risk factors, mainly for CVD, can increase the number of unfavorable outcomes [21]. Thus, it is necessary conducting analyses focusing on the correlation between these factors to enable performing more effective interventions based on multiple components.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of individual risky behaviours were significantly associated with each other, supporting recommendations from Hale and Viner (2016) and a systematic review by Meader et al (2016) to target MRBs concurrently [ 6 , 8 ]. Whitaker et al (2021) found that substance use such as alcohol consumption, smoking and illegal drugs clustered in unhealthy adolescents, while risky sexual activity and gambling typically occurred in isolation [ 42 ]. By contrast, this study finds reduced odds in alcohol consumption with vaping and gambling, suggesting that adolescents who drink may not engage in other risky behaviours.…”
Section: Discussionmentioning
confidence: 99%